PERANAN BADAN USAHA MILIK DESA (BUMDES) ARWANA MAHATO DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI DESA MAHATO - Neli Alpina (Jurnal Ilmiah Cano Ekonomos, 2023)
The development of the economic base of Mahato Village is carried out by the village government throughvarious programs with the aim of community welfare. This research aims to know the form of BUMDes business units, the contribution of BUMDes in the rural economy, and obstacles in managing BUMDes in Mahato Village. This research uses descriptive survey method based on primary and secondary data, with data collection through interviews and documentation studies. The research results show that the form of the unit The Arwana Mahato BUMDes business in Mahato Village is the Village Economic Business Savings and Loans (UEDSP) and LPG Gas Cylinder Sales Base. BUMDes Arowana Mahato contribute to improving the economy of the Mahato community through various types of business units, including: (a) Capital Borrowing, (b) Opening Fields Employment, and (c) Raising Laying Chickens. Mahato Village BUMDes cannot yet be implemented such as the purpose of the establishment and its objectives. This happens because there are still a lot of them Obstacles that occur in this institution include: (a) Lack of capital owned by BUMDes, (b) Lack of HR skills and abilities in managing BUMDes, and (c) lack of public knowledge about BUMDes and minimal participation public.